2018
DOI: 10.20944/preprints201806.0083.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Early Developmental Exposure to General Anesthetic Agents in Primary Neuron Culture Disrupts Synapse Formation via Actions on the mTOR Pathway

Abstract: Human epidemiologic studies and laboratory investigations in animal models suggest that exposure to general anesthetic agents (GAs) have harmful effects on brain development. The mechanism underlying this putative iatrogenic condition is not clear and there are currently no accepted strategies for prophylaxis or treatment. Recent evidence suggests that anesthetics might cause persistent deficits in synaptogenesis by disrupting key events in neurodevelopment. Using an in vitro model consisting of dissociated pr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 37 publications
1
11
1
Order By: Relevance
“…Male and female pups were euthanized at birth or on post‐natal day 1 by decapitation using sterile scissors following cold‐induced anesthesia. This method of anesthesia was chosen over CO 2 or chemical sedatives because neonatal pups are resistant to CO 2 ‐induced anesthesia (Duffy et al ), and common chemical sedatives they are known to interfere with neuronal morphogenesis (Xu et al ). Euthanasia was performed between 8 am and 12 noon.…”
Section: Methodsmentioning
confidence: 99%
“…Male and female pups were euthanized at birth or on post‐natal day 1 by decapitation using sterile scissors following cold‐induced anesthesia. This method of anesthesia was chosen over CO 2 or chemical sedatives because neonatal pups are resistant to CO 2 ‐induced anesthesia (Duffy et al ), and common chemical sedatives they are known to interfere with neuronal morphogenesis (Xu et al ). Euthanasia was performed between 8 am and 12 noon.…”
Section: Methodsmentioning
confidence: 99%
“…29 A growing body of literature further describes mTOR-dependent anesthesia-induced effects in neurodevelopmentally immature rodents. Mintz and colleagues 32,33 have demonstrated in mouse models that isoflurane anesthesia is capable of eliciting abnormal dendrite arbor and spine development, pre-and postsynaptic marker expression, and also deficiencies in spatial learning and memory. These effects were all blocked by rapamycin administration.…”
Section: Isoflurane: Persistent Changes In Neuron Dynamicsmentioning
confidence: 99%
“…Amounts of studies implied that resveratrol could influence autophagy, oxidative stress, and inflammation through the mTOR pathway [49,[82][83][84]. Additionally, the mTOR pathway was found to take part in the regulation of dendritic growth, synapse formation, and synaptic protein expression [85][86][87]. It was reported that general anesthetics, including sevoflurane, induced developmental neuronal injury by activating the mTOR pathway [87][88][89][90].…”
mentioning
confidence: 99%
“…Additionally, the mTOR pathway was found to take part in the regulation of dendritic growth, synapse formation, and synaptic protein expression [85][86][87]. It was reported that general anesthetics, including sevoflurane, induced developmental neuronal injury by activating the mTOR pathway [87][88][89][90]. In light of the fact that mTOR and BDNF interact in a complicated way in physiological or pathological settings [91,92], we did not explore the crosstalk between BDNF and mTOR signaling in the sevoflurane-induced injury in the present study.…”
mentioning
confidence: 99%